2020
DOI: 10.1107/s205225252000233x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural pathway of conformational polymorph nucleation by comparing a series of α,ω-alkanedicarboxylic acids

Abstract: Herein the nucleation pathway of conformational polymorphs was revealed by studying the relationships and distinctions among a series of α,ω-alkanedicarboxylic acids [HOOC–(CH2) n−2–COOH, named DAn, where n = 5, 7, 9, 11, 13, 15] in the solid state and in solution. Their polymorphic outcomes, with the exception of DA5, show solvent dependence: form I with conformation I crystallizes from solvents with hydrogen-bond donating (HBD) ability, whereas form II with conformation II crystallizes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
(66 reference statements)
2
20
0
Order By: Relevance
“…Also, the higher the concentration of glutaric acid, the higher the intensity ratio of the 1712–1740 cm –1 band. This supports that the carboxyl group of glutaric acid self-assembles in ethyl acetate after reaching a certain concentration, and the degree of aggregation increases with increasing concentration, ,, suggesting that the intermolecular interaction of solutes is not intramolecular.…”
Section: Results and Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Also, the higher the concentration of glutaric acid, the higher the intensity ratio of the 1712–1740 cm –1 band. This supports that the carboxyl group of glutaric acid self-assembles in ethyl acetate after reaching a certain concentration, and the degree of aggregation increases with increasing concentration, ,, suggesting that the intermolecular interaction of solutes is not intramolecular.…”
Section: Results and Discussionsupporting
confidence: 62%
“…Different solvents, which possess different hydrogen-bond donating (HBD) and hydrogen-bond accepting (HBA) abilities, are represented by α and β, respectively. It was confirmed in the Shi et al article that there were significant differences between solute species in solvents with different HBD capacities. A lack of HBD capacity provides more opportunities for solute self-aggregation.…”
Section: Results and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarity analysis of the solute crystal and template There are usually two conformational polymorphs that exist under environment conditions. Different carboxyl torsions at both ends of the diacid molecules [(O 2 -C 1 -C 2 -C 3 and O 4 -C n -C nÀ1 -C nÀ2 ) are named 1 and 2 , respectively] result in different molecular conformations (Shi et al, 2021(Shi et al, , 2020. However, the carboxyl torsions of form II of a series diacids with different carbon chains are similar, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Odd-carbon ,!alkanedicarboxylic acids (diacids) usually have two conformational polymorphs under normal conditions, whose carboxyl torsions at both ends of the molecule are different (Shi et al, 2018). Our previous studies demonstrated that the stable or metastable polymorph of a series of diacids with different carbon chain lengths shared a similar crystal structure (Shi et al, 2020). Meanwhile, we found that their solubility decreased sharply with increasing chain length, especially in water.…”
Section: Introductionmentioning
confidence: 92%